Allied health medical imaging and radiotherapy technologists: studies on leadership - Martins, Amadeu Manuel Rodrigues Cardoso (2019)
FIRST ABSTRACT - Purpose: Allied Health Professionals (AHP) form a large part of the workforce in health care and play a central role in diagnosis and therapeutic procedures. Leadership outcomes in allied health professionals are unclear and not thoroughly studied. This article consists of a systematic review of leadership outcomes on allied health professionals globally. Methodology: This was a systematic review of the literature on PubMed, B-ON, ScienceDirect, and Scopus databases, using the terms: leadership AND allied health professions. This research was restricted to articles published between 2008 and 2018. Findings: 746 papers were retrieved; 11 met the inclusion criteria. The included literature varied in quality and design, being 9 quantitative studies and 2 qualitative studies. After thematic analysis, leadership outcomes were obtained and put together in three major areas: characteristics of the leaders, barriers to leadership, and the need for improvement. Value: This systematic review adds to the growing body of evidence and indicates that leadership has been studied to identify and characterize leadership profiles on those professionals. There were highlighted several barriers to leadership that depend on external and internal factors. Additionally, leadership challenges and potential areas of development for leadership training were identified, as well as the implementation of specific leadership programs for each job category and country.